Attitudes toward real analysis and its reflection on academic performance in real analysis - Nurul Faizah Zulkifli,; Adem Kilicman, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Different students perceive the subject real analysis differently. However, the most common perception of real analysis is through four main aspects which are students’ enjoyment, fear, anxiety and distress in learning, usefulness of real analysis in life and perceived achievement in the subject. These perceptions affect how students behave in class during real analysis and subsequently affect their attitudes and academic performance in real analysis. This present work studies the students’ attitudes toward real analysis, their academic performance in real analysis and the relationship between these two attributes. The quantitative data for the present study is collected using the questionnaires of Mathematical Attitude Scale Concise Form (MAS Concise Form) and the Academic Success Inventory for College Students (ASICS) to measure students' attitudes toward real analysis and their academic performance in real analysis respectively. The differences in academic performance in real analysis between male and female students was also studied. Overall, it was found that students displayed moderate attitudes toward real analysis and moderate academic performance in real analysis, and there exists a significant relation between attitudes toward real analysis and academic performance in real analysis. However, it was found that there is no relation between students’ gender and their academic performance in real analysis.